Aggregation-induced emission of triphenyl-substituted tristyrylbenzenes - Zhang, Hao; Rominger, Frank; Bunz, Uwe H. F.; Freudenberg, Jan (Chemistry - a European journal, 2019)
The synthesis, properties and X-ray single-crystal structures of two regioisomeric triphenyl tristyrylbenzenes are reported. Both C3v and Cs derivatives display aggregation-induced emission (AIE) behavior. Regioisomerism impacts the solid-state intermolecular interactions, the photophysical characteristics and photostability in solution.